2006
DOI: 10.1007/s00296-006-0231-3
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of Tropheryma whippelii DNA in saliva from healthy controls and patients with spondyloarthropathy

Abstract: Whipple's disease (WD) is a chronic infectious disorder of multi-system caused by Tropheryma whippelii (TW). Although the prominent symptoms are diarrhea, malabsorption, and weight loss, the arthritis may precede the gastrointestinal symptoms [1]. Furthermore, some cases of WD shows the clinical manifestations of spondyloarthropathy (SpA), such as oligoarthritis pattern, axial involvement, sacroiliitis, and association with HLA-B27 [2].The presence of periodic acid-SchiV-staining foamy macrophages in the lamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 6 publications
1
5
0
Order By: Relevance
“…Similar to previous Korean studies conducted with saliva, T. whipplei was detected low in the stools of patients with diarrhea, with a prevalence of 1.4% [ 22 , 23 ]. A recent study investigating the stools of patients with diarrhea for T. whipplei in three locations on different continents reported that its prevalence may differ between continents [ 26 ].…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…Similar to previous Korean studies conducted with saliva, T. whipplei was detected low in the stools of patients with diarrhea, with a prevalence of 1.4% [ 22 , 23 ]. A recent study investigating the stools of patients with diarrhea for T. whipplei in three locations on different continents reported that its prevalence may differ between continents [ 26 ].…”
Section: Discussionsupporting
confidence: 83%
“…This study provides baseline data about the presence of T. whipplei in the stools of Korean patients with diarrhea because it was performed on a large cohort including all ages. In addition, positive controls that were not used for PCRs in previous Korean studies were used in this study [ 12 , 22 , 23 ]. Without positive controls for the PCRs, inaccurate results may have been obtained.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As far as we aware no one has investigated T . whipplei fecal carriage in Asia, but it has been detected in Korea among 1.5% of healthy peoples’ saliva, but not in any of 108 small-bowel biopsies in Malaysia or in any of ten marginal supragingival plaque samples from Chinese patients with gingivitis [ 17 , 18 , 20 ]. In rural Senegal, the first contact with the bacterium occurred mainly in children before 4 years of age, with the prevalence of T .…”
Section: Discussionmentioning
confidence: 99%